Optimizing Speaking Abilities of Business Management Students of Manado State Polytechnic through English as a Medium Instruction (EMI) - Walangitan Melania Rut; Reski Amalia S; Mega Fitri Wulandari (Hasanuddin University, 2024)
This study explores the optimization of speaking abilities among Business Management students through the implementation of English as a Medium Instruction (EMI). With the increasing global demand for effective communication skills in the business environment, enhancing students' speaking proficiency is important. This study employed qualitative research in which the data was collected using an observation checklist for Business Management students, especially in the class of IV MB 6. Results indicate that EMI not only improves students' confidence in speaking but also enhances their fluency and overall communicative competence. Furthermore, the study highlights the importance of interactive teaching strategies and real-world applications in fostering an engaging learning environment. Students are encouraged to speak English in groups or respond the other speaker as they move through the material. Students practice language skills in context through discussions and projects, which improves their comprehension of the material and their ability to communicate ideas in English. The findings suggest that EMI can be an effective pedagogical tool in developing essential speaking skills for future business leaders.